Numerical simulation of tunnel surrounding rock temperature field. Issue 1 (October 2020) - Wang, Yansong; Quan, Qunshan; Zhao, Yuguo; Zhang, Zhongzhe; Jiang, Xinghong
Abstract: Severe freezing injury can lead to tunnel encroachment and affect the safety of tunnel operation. The temperature field of surrounding rock and lining can be changed obviously by laying insulation layer on the outside surface of tunnel lining. Taking Wunvfeng tunnel as the engineering background. ANSYS program is used to simulate the surrounding rock temperature field, by comparing the two cases with and without protective layer, the variation law of surrounding rock temperature with time and space is obtained.